Ethnicity and Political Behaviour During Nigeria’s 2023 Presidential Election - Ezedikachi, Eze-Michael Ezedikachi; Ogunsanya, Opeyemi Erioluwa Ogunsanya (African Journal of Stability and Development (AJSD), 2025)
Ethnicity has historically played a significant role in shaping political behaviour around the world, influencing government structures, political systems, and political mobilisation. This has encouraged the engagement of ethnic politics, especially during elections. The 2023 Nigerian presidential election further demonstrated the influence of ethnicity in Nigeria’s politics. Ethnic sentiment in political behaviour has been influential in furthering ethnic politics, ethnic violence, and ethnic loyalty to the detriment of national unity and development. This study examined the ongoing influence of ethnicity on political behaviour, using the 2023 presidential election in Nigeria as a case study. The study adopted social identity theory and Instrumentalism theory. This research employed a mixed-methods approach, combining qualitative interviews with quantitative surveys. This study employed multi-sampling techniques, which included clustered, purposive and accidental sampling techniques. The research found that ethnicity has a notable influence on the political behaviour of citizens, especially in Nigeria’s 2023 presidential election. However, the influence is based on factors like ethnic-driven campaigns, ethnic loyalty and interest, which illuminated the dynamic nature of ethnicity as both a unifying and divisive force in Nigeria’s political system. The paper concluded that ethnicity remains a double-edged sword, mobilising tribal loyalties while fuelling violence through the employment of ethnic favouritism and exclusion. The study recommends that Nigeria’s government should enforce legal frameworks to penalise political actors who promote ethnic-based campaigns.